The effect of e-filing and e-billing implementation and understanding self assessment system against registered WPOP compliance - Yanti, Yulia Febri; Asmapane, Set (INOVASI: Jurnal Ekonomi, Keuangan, dan Manajemen, 2023)
This study aims to determine the effect and evidence that the implementation of e-Filing and e-Billing as well as Understanding the Self Assessment System on WPOP compliance (Individual Taxpayers) registered at KPP Samarinda Ulu. This type of research is quantitative using data from taxpayer respondents measured on a likert scale of 1-5. The sample size was 100 individual taxpayer respondents at KPP Pratama Samarinda Ulu. This research uses the PLS-SEM method with the SmartPLS 3.0 program. The results of this study show that e-Filing has a significant positive effect on WPOP Compliance, e-Billing has a significant positive effect on WPOP Compliance and Understanding the Self Assessment System has a significant positive effect on WPOP Compliance